2016
DOI: 10.1016/j.cub.2015.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Cohesion Established by Rec8-Cohesin in Fetal Oocytes Is Maintained without Detectable Turnover in Oocytes Arrested for Months in Mice

Abstract: SummarySister chromatid cohesion mediated by the cohesin complex is essential for chromosome segregation in mitosis and meiosis [1]. Rec8-containing cohesin, bound to Smc3/Smc1α or Smc3/Smc1β, maintains bivalent cohesion in mammalian meiosis [2, 3, 4, 5, 6]. In females, meiotic DNA replication and recombination occur in fetal oocytes. After birth, oocytes arrest at the prolonged dictyate stage until recruited to grow into mature oocytes that divide at ovulation. How cohesion is maintained in arrested oocytes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 40 publications
(55 reference statements)
3
68
0
1
Order By: Relevance
“…2B, model 2). Similarly, cohesion is established in pre-meiotic S-phase without detectable cohesin turnover during prophase I [17]. Further, both the WT and KO groups retain ~70% of the CENP-A protein seen in the young C57BL/6J group, showing that the majority of CENP-A present since early prophase I arrest in the primordial follicle is retained at the centromere for ~1 year.…”
Section: Resultsmentioning
confidence: 99%
“…2B, model 2). Similarly, cohesion is established in pre-meiotic S-phase without detectable cohesin turnover during prophase I [17]. Further, both the WT and KO groups retain ~70% of the CENP-A protein seen in the young C57BL/6J group, showing that the majority of CENP-A present since early prophase I arrest in the primordial follicle is retained at the centromere for ~1 year.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, centromeric SOLO/SUNN can only be loaded prior to meiotic prophase. Sister-chromatid cohesion in mitotic cells is established during S-phase [36] and in mammals, Rec8 cohesin cannot be replenished and dissociates with age [15, 16, 37]. Whereas in mitotic cells the dynamic and stable cohesin complexes involve the same four core subunits, in meiosis, there may be separate cohesin complexes that differ in their regulation and capacity to be replaced or replenished.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Scc1 protein is efficiently depleted and sister chromatid cohesion fails to be established in Scc1 Δ(m)/+(p) zygotes (hereafter referred to as Scc1 Δ according to the maternal allele; see Fig EV3B and Ladstätter & Tachibana-Konwalski, 2016). Since sister chromatid cohesion is maintained by Rec8-cohesin in oocytes (Tachibana-Konwalski et al, 2010;Burkhardt et al, 2016), Scc1 depletion has no effect on chromosome segregation prior to fertilization, and therefore, a clean Scc1-cohesin knockout zygote is generated.…”
Section: Cohesin Is Essential For Zygotic Chromatin Folding Into Loopmentioning
confidence: 99%